SIKAP KEPRIBADIAN MORAL DALAM MEWUJUDKAN KEHIDUPAN BERMASYARAKAT DAN PELAJAR YANG BERETIKA - Fadil Masud, S.Sos., M.Hum; Anjulin Yonathan Kamlasi,M.Pd; Asri Laksenia Tamonob; Adrianus Seso; Sarni Sain; Klarinta Victoria Bayfeto; Dewi Astuti S. Saleh (STKIP Subang, 2025)
Rapid social change and the development of digital technology have created serious ethical challenges in social life and among students. Declining social awareness, unethical communication practices, and the misuse of social media indicate the importance of strengthening moral personality attitudes as the foundation of ethical behavior. This study aims to analyze the role of moral personality attitudes in fostering ethical social life among society and students. The research employed a Systematic Literature Review (SLR) method by examining relevant academic articles obtained from Google Scholar published over the last ten years. Data were analyzed through identification, selection, and narrative synthesis of research findings. The results indicate that moral personality attitudes play a crucial role in shaping responsible, tolerant, and ethical behavior in both real-life and digital social interactions. Strengthening moral personality through moral education and digital literacy contributes significantly to reducing unethical behaviors such as the spread of misinformation, hate speech, and intolerance. Therefore, continuous development of moral personality attitudes through education, family, and community involvement is essential to create ethical and civilized social and student life.